(untitled) - Bednarikova, Janka (Aura musica, 2021)
The current generation of seniors is experiencing their social status with much more difficulty than one could imagine. Seniors often feel lonely, unnecessary, useless, and without meaning and fulfillment in their lives. One of the activities that can at least partially alleviate these negative feelings is the international project ASEB. The project, Active Senior Education without Barriers, was created at the University of Ostrava (in Ostrava) within the European Erasmus + programs focused on adult education and including seniors. The following article will introduce the project and describe its focus, goals, and main pillars of its implementation.
Keywords: ASEB; The University of the Third Age; Education of Seniors; International Cooperation; Choral Singing